Perancangan Catu Daya Dengan Penambahan Panel Surya Pada Smart Traffic Light - Hadisyahputra, Fauzan; Marpaung, Novery Lysbetti (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Recently Indonesia is one of the countries with a densely populated of population. Besides it, using of vehicles causes traffic jam in many cities, including Pekanbaru. Power outages be one of causers of traffic jam due to many traffic lights do not working properly. In this study, the authors designed a power supply that is able to keep the traffic lights on when electricity from National Electricity Company (PLN) is not active. In this case, there is addition of solar panels so the traffic light can be on for few hours during the supply of PLN is inactive. The used load is a prototype of smart traffic light (STL) 80Watt under PLC control. Battery is used 12V7Ah which filled by Solar Panel. When supply from PLN is off, relay works and the load source automatically switches to Battery. To increase output voltage of Solar Panel, Boost Converter is added to this design to gain 24V. From switching time of PLN to battery take 0,08s, so the traffic lights have no chance to be inactive. This research works as framework well.Keywords: boost converter, solar cell, power supply, switching.